Dynamic Analysis of Electro Hydrostatic Actuation System. (2016) - Navatha, A.; Bellad, Kiran; Hiremath, Somashekhar S.; Karunanidhi, S.
Abstract: More electric aircraft initiative has led to Fly-By-Wire (FBW) and Power-By-Wire (PBW) technologies. PBW technology has several advantages and has potential for weight reduction and energy saving compared to conventional hydraulic system. Recent development in aviation technology have combined the electric and hydraulic system and arrived at high performance Electro Hydrostatic Actuator (EHA) system. It is a one of the PBW technology which aims at replacing the centralized hydraulic system by a local self-contained and compact actuator system. It is an emerging technology which combines the benefits of conventional hydraulic system and direct drive actuators, like the high energy efficiency, high dynamic response, high torque to mass ratio and high maintainability. EHA system was initially introduced in aircraft for flight control system. Most of the current research literatures considered the EHA system with symmetric actuator configuration. This is because, most of the aircraft application uses symmetric cylinder. However in case of industrial application, asymmetric actuators are predominantly used. An indigenous experimental setup of EHA system with asymmetric actuator has been developed with sensors and instrumentation. In this paper, the dynamic analysis, position tracking and control of the EHA system by varying the speed of drive motor has been established using a Proportional Integral Derivative (PID) controller. PID tuning has been done using Ziegler Nichols (ZN) method. The response using of Proportional Integral (PI), Proportional Derivative (PD) and PID controllers has been studied and found that the PD controller gives the best response.